TANDA IKON DALAM KOMIK ONE PUNCH MAN KARYA ONE SUATU ANALISIS SEMIOTIK - MANALIP, RIVANDY (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2016)
ABSTRACT This research which entitled â€œTanda Ikon Dalam Komik One Punch Man Karya One Suatu Analisis Semiotikâ€ is focused on icon that can be found in the comic One Punch Man. The aims of this research are to identify kinds and forms of icon in the comic One Punch Man and to analyze the meaning of each frame in the comic One Punch Man. This research uses the McCloud and Zoestâ€™s theories in the process to identifying kinds and forms of icon and to analyze the meaning of each frame in the comic One Punch Man uses Bergerâ€™s theory. The method of this research is descriptive. Every icon that can be found in the comic were identified and classified into four forms of icon which are human icon, animal icon, object icon, onomatopoeia icon and three kinds of icon which are typological icon, diagrammatic icon, and metaphoric icon. Then, every frame in the comic were analyzed by using Bergerâ€™s Theory. The result of this research shows that there are 42 human icon, 7 animal icon, 24 object icon, and 7 onomatopoeia icon, according to kinds, typological icon contained in 18 frame, diagrammatic icon contained in 30 frame and metaphoric icon contained in 30 frame. And every meaning in the comic One Punch Man is different from each other. ______________________________________________________________________ Keyword: Icon, Comic, One Punch Man, Semiotics Analysis